HUBUNGAN ANTARA NUTRITION LITERACY DENGAN KEJADIAN ANEMIA PADA PEGAWAI UGM - , ANINDITA DWI PUTRANTI, Dr. Toto Sudargo, SKM., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Anemia is the most common deficiency in Indonesia. The prevalence of anemia in Indonesia is 21,7%. Children, women, and worker are the group risk of anemia. Contributing factors which may cause anemia are sudden lost of blood, increased body requirement, and deficiency some nutrition such as iron, protein, and vitamin C. The other contributing factors are gender, age, education, knowledge, and social economic. Decresed work capacity is one health consequences of anemia. Nutrition literacy is related to someone knowledge about nutrition and it needed to make appropriate health decisions. Someone nutrition knowledge can be observed based on someone dietary intake. Aim : The aim of this study is to determine the relationship between nutrition literacy and anemia among staff of Universitas Gadjah Mada which doing general check up at GMC Health Center. Methods : The study was observational with cross sectional design. Subjects for the study were 97 peoples which were selected using consecutive method sampling on staff of Universitas Gadjah Mada who did general check up at GMC Health Center. Variabel for this study were nutrition literacy, protein intake, iron intake, vitamin C intake, and anemia. Nutrition literacy was obtained by filling nutrition literacy assessment instrument (NLAI) questionnaire. Protein, iron, and vitamin C intake were obtained by filling semi quantitative-food frequeny questsionnaire (SQFFQ). Hemoglobin levels were obtained from general check up data. Relationship analyze using fisherâs test and correlation analyze using spearman test. Results : There is no relationship between nutrition literacy and anemia (p>0,05). There is a relationship between nutrition literacy and iron intake, and also between iron intake and anemia (p<0,05). There is neither relationship between nutrition literacy and protein intake nor between nutrition literacy and vitamin C (p>0,05). There is neither relationship between protein intake and anemia nor vitamin C intake and anemia (p>0,05). Conclusion : There is no relationship between nutrition literacy and anemia among staff of Universitas Gadjah Mada. Keywords : Anemia, Nutrition Literacy, Dietary intake